Folate Biofortification in Soybean: Challenges and Prospects - Kwadwo Gyapong Agyenim-Boateng; Shengrui Zhang; Md. Jahidul Islam Shohag; Abdulwahab S. Shaibu; Jing Li; Bin Li; Junming Sun (Agronomy, 2023)
Folate deficiency is a significant global health issue that affects millions of people and causes severe adverse effects. Major staple crops, which provide significant amounts of calories, often contain inadequate folate levels. Synthetic fortification has contributed to a reduction in low-folate populations, but a more sustainable solution is needed. Biofortification, or the breeding of crops to naturally increase their nutrient content, is a promising alternative. Soybean is a highly nutritious crop and a good candidate for folate biofortification. However, studies on folate have been limited due to the challenges in folate analysis. The development of sensitive and selective tools, reference materials, and studies on the stability of folate vitamers in crops has facilitated the development of improved folate determination methods. Additionally, the soybean folate biofortification program can be improved by leveraging previous studies in major cereals, common bean and pea, as well as combining conventional breeding with new genomics approaches. In this review, we discuss the folate content, composition, and analytical challenges in soybean and suggest possible frameworks and strategies for folate biofortification in soybean. We also conducted an in silico analysis of key folate biosynthesis enzymes in soybean.